Application and Performance Evaluation of Model Predictive Controllers on Driving Force Based Reactive Distillation Processes (Chemical Engineering Research Bulletin, 2021)
In this work, integrated design and control of Reactive Distillation (RD) column operating under Model Predictive Controller (MPC) is presented. At first, a design target is defined, and the RD column is designed based on the element concept at the maximum driving force. After that, the steady state simulation is carried out in ASPEN PLUS that satisfies the design target. Next, the flow driven dynamic system is linearized in ASPEN PLUS Dynamics and the state space matrices are obtained. Using the matrices, MPC closed-loop simulation is carried out in MATLAB. To quantify both the steady state and dynamic operation, a multi objective function is defined that takes into account both the design (total energy consumption, total carbon footprint), and the control performance (Integral Absolute Error, total variation of input, relative gain array, Niederlinski Index). For further verification, an alternative design based on non-maximal driving force is also obtained, and the corresponding steady state and dynamic simulation is performed. The closed-loop performance of MPC controller under feed disturbance shows that the process that is designed at the maximum driving force exhibit better control performance compared to the design alternative that does not take into account the maximum available driving force.Chemical Engineering Research Bulletin 21(2020) 49-53